2021
DOI: 10.1111/tri.14015
|View full text |Cite
|
Sign up to set email alerts
|

Extraperitoneal kidney transplantation: a comparison between children weighting ≤15 kg and >15 kg. Experience of a single institution

Abstract: Extraperitoneal approach is sometimes recommended for kidney transplantation (KT) in children weighting <15 kg. We hypothesized that this approach might be as successful as in patients with normal weight. Data of all consecutive KTs performed between 2013 and 2019 were retrospectively reviewed. Early outcomes and surgical complications were compared between children weighing ≤15 kg (low-weight (LW) group) and those weighing >15 kg (Normal-weight (NW) group). All the 108 KTs were performed through an extraperit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…Finally, a total of 23 studies were included in this systematic review (Fig. 1) [9][10][11]12,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Search Resultsmentioning
confidence: 99%
“…Finally, a total of 23 studies were included in this systematic review (Fig. 1) [9][10][11]12,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Search Resultsmentioning
confidence: 99%
“…Similarly, patient survival appeared to rapidly decline particularly in the <8.6 kg weight group in the immediate post‐transplant period. Several other single‐center studies have examined outcomes in children <15 kg 21–24 . Two studies comparing children <15 kg and those ≥15 kg showed that there was no difference in allograft outcomes based on weight at the time of transplant 22,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Two studies comparing children <15 kg and those ≥15 kg showed that there was no difference in allograft outcomes based on weight at the time of transplant 22,24 . One study showed that recipients with a weight <15 kg at the time of transplant were associated with an increased occurrence of venous thrombosis 21 . A more recent larger study used the UK Transplant Registry and found significantly improved allograft survival over a 10‐year follow‐up period in children <15 kg at the time of transplant when compared to children ≥15 kg (85.4% vs. 73.5%; p = .002) 25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations